Analysis of Prevention Behavior Vaginal Discharge Based on the Theory of Health Promotion Model (HPM) in Grade XII Students of State High School 4 Jambi City - Wahidah Marwiyah, Siti; Astuti Siregar, Sri; Kasyani, Kasyani; Herwansyah, Herwansyah; Rifqi Azhary, Muhammad (Jurnal KESANS : Kesehatan dan Sains, 2025)
Reproductive health is an issue that is currently the focus of attention in adolescents. WHO states that 45% of women have experienced vaginal discharge at least twice and 90% of women in Indonesia have the potential to experience vaginal discharge so it is necessary to prevent vaginal discharge which can be done by using the Health Promotion Model). This study aims to analyzing factors associated with vaginal discharge prevention behavior based on the Health Promotion Model (HPM) theory in Class XII State High School 4 Jambi City. This study is a cross-sectional study. The research subjects were XII grade students of State High School 4 Jambi City (n = 152) There is a significant relationship between self-motivation, perceived benefits, and self-commitment with vaginal discharge prevention behavior (p value < 0.05). However, no significant relationship was found between interpersonal influence and vaginal discharge prevention behavior (p value > 0.05). This study shows that self-motivation, perceived benefits, and self-commitment are significantly related to preventive behavior against vaginal discharge, while interpersonal influence is not.